1996
DOI: 10.1093/jn/126.suppl_4.1192s
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Vitamin K to Bone in Humans

Abstract: Molecules with vitamin K activity are important for optimal bone health. The major compound of this group in bone is vitamin K1 (phylloquinone), which is derived exclusively from plant foods in the diet. Vitamin K1 is absorbed along with dietary fat from the small intestine and transported by chylomicrons in blood. In serum obtained after an overnight fast from healthy men more than half of the vitamin K1 was recovered from the density fraction that contains chylomicrons and chylomicron remnants (CR), and only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 20 publications
3
85
0
1
Order By: Relevance
“…Chylomicron uptake and clearance are affected significantly by APOE genotype, 25 leading to marked fluctuations in plasma concentrations of vitamin K1. 26 Low vitamin K1 levels have been measured, especially in patients carrying the e4 allele 26 and are associated with a poor outcome in hemorrhagic stroke patients. 27 Thus, possible interactions between APOE variants and vitamin K1 metabolism might be related to the risk of IS independently of the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chylomicron uptake and clearance are affected significantly by APOE genotype, 25 leading to marked fluctuations in plasma concentrations of vitamin K1. 26 Low vitamin K1 levels have been measured, especially in patients carrying the e4 allele 26 and are associated with a poor outcome in hemorrhagic stroke patients. 27 Thus, possible interactions between APOE variants and vitamin K1 metabolism might be related to the risk of IS independently of the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…60 Vitamin K 1 is absorbed from the small intestine along with dietary fat, transported by chylomicrons in the blood and subsequently cleared by the liver through an APOE receptorspecific uptake. [61][62][63] Uptake of chylomicrons and thus vitamin K 1 into the liver varies between different APOE alleles, the rank order being *E44*E34*E2. 61,64 Consistent with this, patients with the APOE*E2 allele, who allegedly have the least efficient uptake of vitamin K 1 , have an increased risk of warfarin-associated intracerebral haemorrhage.…”
Section: Biotransformation Of Warfarinmentioning
confidence: 99%
“…[61][62][63] Uptake of chylomicrons and thus vitamin K 1 into the liver varies between different APOE alleles, the rank order being *E44*E34*E2. 61,64 Consistent with this, patients with the APOE*E2 allele, who allegedly have the least efficient uptake of vitamin K 1 , have an increased risk of warfarin-associated intracerebral haemorrhage. 65 In a Swedish cohort, it was shown that CYP2C9*1/ *1 individuals (extensive metabolizers) who were homozygous for APOE*E4 were given significantly higher warfarin doses than other CYP2C9 extensive metabolizers.…”
Section: Biotransformation Of Warfarinmentioning
confidence: 99%
“…Allison AC (Allison, 2001) proposed a possible role of vitamin K deficiency in the pathogenesis of AD and in augmenting brain damage associated with cerebrovascular disease, based on the potential actions of vitamin K in the brain and through a link to the apolipoprotein E genotype. The apolipoprotein E4 allele, an established risk factor for AD (Mattson, 2004), strongly influences plasma vitamin K levels (Kohlmeier M, 1996;Saupe J, 1993). Thus, carriers of apolipoprotein E4 allele could also those with the lowest vitamin K concentrations, an association that has not yet been investigated.…”
Section: Vitamin Kmentioning
confidence: 99%